Evaluasi dan Perbaikan Proses Bisnis pada Divisi Operasional PT. Ventika Terra Semesta Menggunakan Teknik ESIA - Apriyanti Apriyanti; Ismiarta Aknuranda; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Ventika Terra Semesta is a company property developer in Malang that engaged on housing developer. One of the divisions on PT. Ventika Terra semesta is operational division. Operational division on duty for doin development. Development is one of core activities of PT. Ventika terra semesta. Based on the result of interviews with part of PT. Ventika terra semesta there is a problem on operational division. That problem is often occur of delay in development. In one year happened five times of delay in development. This result is customer complains and delay in repayment for house. When that problem not immediately resolved, the customer will move to order house to the competitors, so that will decrease the provit of PT. Ventika terra semesta. Based on the problems is modeling needs to be done and business process analysis to find out the cause of problems so can provide a suggestion of business process in order to improve the time efficiency.To doing business process modeling on this research uses BPMB (Business Process Modelling and Notation). To get a better business process can be uses business process improvement methode(BPI). To find of activities on business process which needs to be repaired, that use the technique of ESIA ( Eliminate, Simplify, Integrate, Automate). Simulation results of material purchasing business process has a decreased time is amounting to 62% or 7 days 13 hours 2 minutes 29 seconds.